Are Allied Health Professionals (AHPs) research ready? A regional evaluation in England: the Research ABC project (AHPs Building Research Capacity Across the Black Country) - Ali Aries; Roanna Burgess; Louise Wallace; Tina Hadley-Barrows; Amy Palmer; Rosalind Leslie (BMC Medical Education)
Abstract Background Research active organisations achieve better healthcare outcomes. The Research ABC Project (Allied Health Professions (AHPs) Building Research Capacity Across the Black Country), funded from 1/8/23–31/3/24 by a Clinical Research Network West Midlands Improvement and Innovation grant, was commissioned to facilitate the Black Country Integrated Care System to address the four domains of Health Education England’s AHPs’ Research and Innovation Strategy for England (capacity, capability, context and culture). This evaluation aimed to understand research-readiness, initiate research skills development through bespoke training, increase research capacity of the local AHP Community and inform the Integrated Care Board of future requirements. Methods AHPs in six Black Country NHS Trusts, West Midlands, United Kingdom (n = 2396) were invited to participate in a cross-sectional survey via Microsoft forms (October–November 2023). Baseline levels of engagement in research activities, existing research skills, barriers to engagement, and training needs were explored. Descriptive analysis and thematic analysis for free text answers were undertaken. Project outputs included bespoke training, shared digital space, and Research Champions identification and support; success of the project was evaluated. Results There were 440 eligible responses from 11 of 14 professions (response rate 18.4%) with over half qualified > 10 years. Qualifications ranged from diploma (5.9%), degree/BSc (40.2%), postgraduate credits (27.0%), and MSc (24.6%) to PhD (0.9%). Research outputs were limited: 85.9% had no publications, 83.8% no abstract submissions; only 6.8% had Chief/Principal Investigator experience. However, audit (83.6%), service evaluation (75.9%), and quality improvement (78.9%) activities were common. Main barriers to research engagement were work pressures (42%), commitments outside work (22%), deemed not applicable (14%), not supported (8%), and not interested (7%). Training needs and Research Champions (n = 93) were identified. Training sessions (n = 23) were attended by 169 AHPs and well-evaluated. The digital space facilitated networking (285 AHPs signed-up). Conclusions The Research ABC project identified baseline research levels for AHPs across the Black Country, and delivered training, with potential to develop research capability and capacity. Research Champions enable research, creating a supportive environment (context) and changing culture, addressing the AHP Research Strategy vision. The Research ABC model and GO-RESEARCH recommendations (developed from the project findings) could be adopted more widely to help drive AHP research forward; appropriate infrastructure and raising the importance of research is essential to achieve this in the future.